KEDUDUKAN KETERANGAN KORBAN PEMERKOSAAN YANG MENGALAMI KETERBELAKANGAN MENTAL DALAM PROSES PEMBUKTIAN di TINGKAT PENYIDIKAN OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Mukhtal Lutfi; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The problem of sexual violence (rape) is one form of crime that harasses and tarnish the dignity, it should be categorized as a type of crime against humanity (crime againts humanity). Rape is not just occur in women and children is normal but it also occurs in women and children mental retardation. In the case of rape victims is a woman who is mentally retarded, and this case also there are irregularities in the investigations, the investigating authorities to inform the family that the investigators did not find the two items of evidence, because the victim suffered mental retardation. Based on the study author, already fulfilling element to rape women mental retardation, namely the documentary evidence and witness testimony evidence, which the witness is a witness victim himself. The purpose of this thesis are: First, How is the implementation of investigation by the investigators in order to find evidence in cases of rape of women mental retardation, Secondly, What is the strength of the evidence victim testimonies in cases of rape of women mental retardation, Third, what are the constraints of the police in gathering evidence cases of rape of mentally retarded womanFrom the research problem there are two main things that can be inferred. First, implementation of investigation terdahap the crime of rape in the City Police Pekanbaru, that in the process of criminal investigation of rape is not working as it should, because it did not carefully and thoroughly so that the presence of the error performance of the investigator handling the case giving rise to dissatisfaction on the part of the victim's family because the perpetrators can not be declared free or snared by the law. Second, as the basis of testimony of the victim, investigators involving experts who have special skills in their field psychologist, to determine whether the information is correct or not their dberikan. After getting assistance in the investigations of the psychologist, the testimony of the victims through the explanation could psychologist dijadian valid evidence. Third, Victim difficult for questioning and could not do a good communication. The absence of witnesses other than the victim, serata difficulty keronologi investigators to determine the incidence of the crime of rape on women who have mental retardation.Keywords : The Victim of rape – mental retardation - KUHP